RUSSIAN CONSERVATISM: MAKING NATIONAL IDEOLOGY AND INFLUENCING RUSSIA’S FOREIGN POLICY - Ivanauskas, Vilius (Politologija, 2016)
The article analyses the impact of present-day Russian internal structural factors, searching national ideology and shaping “Russian conservatism” line formation marked the links between this ideology and Russian foreign policy. The main focus is designated to Russia’s politics after the Russia-Georgia conflict in 2008, highlighting the response of Vladimir Putin’s regime to several domestic policy tensions related with: 1) the structure of the Russian regime and the domination of siloviki group in the power structures; 2) the etno-federalist structure of Russia and the growing nationalism; and 3) the competition of several ideologies, which increasingly turns to the support of Eurasianist ideology line and its transformation into “Russian conservatism”. Theoretically, this analysis is based on the internal and external factors that have an impact on the state’s policies (e.g. Walter Carlsnaes concepts), as well as on the theories analysing Russian etno-federalism and informal networks/relations. This article argues that Russian internal structural factors strongly support the Russian Eurasianist direction as the dominant policy doctrine, and this doctrine defines the Russian foreign policy, limits its balancing and influences the dynamics of foreign policy. It shows how, during the recent years, Russia’s assertive foreign policy has become influenced by neo-imperialist vision of a strong, conservative, and alternative Russia, which actively uses the “Russian conservatism” as an ideological justification, supports active protection of Russia’s interest in the post-Soviet region (e.g., war with Ukraine) increasing the use of foreign policy in the post-Soviet region (e.g., war with Ukraine) or raising the question about the multipolar world order. Other competing ideological lines (pro-Western liberalism and Slavic nationalisms) are still included in the balancing if there is demand, however, it remains non-typical forms of current Russia’s ideological framework. Since the Russia-Georgia war in 2008, the aggressive Russian foreign policy depends not only on the external factors, but it also increasingly reacts to internal factors, especially to Putin’s interest to maintain the vertical power and ensure further legitimacy of the regime. Russia’s “electoral authoritarianism”, which actively used the concept of “sovereign democracy” last decade, faced serious challenges in 2011– 2012. After public protests for electoral fraud, Putin’s circles have perceived that Russia’s ruling elites need to initiate a new turn for the country, either to a wider democracy development or to find other resources to mobilise society. By reacting to the interest of siloviki group and seeing the confrontation between Russian ethnic and minorities’ nationalism manifestations, Putin’s regime strengthened its orientation towards the new Eurasianism, which emphasized the special path of Russia’s civilization: being alternative to the Western world, adjusting only “appropriate for Russia” democracy standards, opposing human rights development, and seeing it as a harmful foreign influence. State patriotism was framed under the new “Russian conservatism” line, which emphasized strong authority of central power, Russian imperial identity, Russia’s interest in Eurasian regions, support for multipolar world, and the spread of conservative values as opposition to Western cosmopolitism. It helped to mobilise Russian society, integrate the great old and the new military victories of Russia’s state and received a new support and greater legitimacy for Putin’s regime. This ideology leaves room for integration of separate narratives from various ideological lines (from the Soviet nostalgia and technocratic modernisation to “old Russia” traditionalism). Military actions in Ukraine in 2014–2015 have illustrated that imperial approach effectively mobilises not only the Russian society but a certain part of the other post- Soviet societies (e.g., the idea of the Russian world). This “Russian conservatism” also attempts to respond to other internal tensions, such as ethnic conflicts, by promoting a more intensive Russian state identity instead of an ethnic identity. The situation, when various ethnic minorities and their leaders (e.g., R. Kadyrov) actively supported Russia’s actions in Ukraine and the new Putin’s activism, revealed that under this ideological umbrella, such local actors as in Putin’s circle, leaders of ethnic regions, Orthodox church, and media authorities find themselves in the state’s ongoing narratives. Under this situation, Putin’s regime effectively marginalises their opponents. Non-systemic liberal-democrats are presented as acting against Russia’s interests. The discourse for keeping the relationship with Western partners, which emphasizes the modernisation or stresses the importance of economic developments, is still valid, and it is still used for balancing, but current ideological trend has clearly prioritised the imperial identity over democracy development.